Immunohistochemistry in pre-invasive vulvar lesions: observations, concerns and an algorithmic approach - Dunaevskaya, V.; Med, V.; Krotevych, M. (Journal of Education, Health and Sport, 2024)
The aim of the study was to investigate the presence of immunohistochemical markers p16, p53 and Ki67 and their diagnostic and prognostic value in women with pre-invasive vulvar lesions such as vulvar high-grade squamous intraepithelial lesions (VHSIL) and differentiated vulvar intraepithelial neoplasia (dVIN). Materials and methods. The results of immunohistochemical (IHC) examination of samples obtained from 253 women diagnosed with HSIL or dVIN who asked for medical care at the National Cancer Institute (Kyiv, Ukraine) in 2017-2023 were analysed. 155 of all women examined were diagnosed with dVIN and 98 with VHSIL. All patients underwent a vulvar biopsy. Histological typing of biopsy samples was performed using routine haematoxylin and eosin staining and immunohistochemical (IHC) examination. The IHC study was performed using monoclonal mouse antibody p16 (Monoclonal Mouse Antibody p16 (Mob575-01)) using the Thermo scientific PA1-16662 system, monoclonal mouse antibody Ki-67 (Monoclonal Mouse Anti-Human Ki-67 Antigen Clone MIB-1 (Dako IR-626)) and monoclonal mouse antibody p53 (Monoclonal Mouse Anti-Human p53 Protein Clone DO-7 (Dako IS-616)) using the EnVisionTM FLEX detection system (Dako, Denmark). Results.The average age of patients with dVIN was 58.26±10.17 years old, and the average age of patients with VHSIL was 39.65±10.22 years old. According to the results of the study, all patients with VHSIL (n=98) had positive staining for Ki67 in the middle and upper epithelial sections, and only 72% (n=71) - for p16. Staining for p53 was negative in all cases. That is, 28% (n=27) of the patients with VHSIL were negative for p16 and positive for Ki67. p53 staining showed the presence of a "wild-type" variant in 65 patients with dVIN (42%) and a "mutant" variant in 90 women (58%). None of the patients showed positive staining for p16. As for VHSIL, the Ki67 marker was detected in 100% of cases and in all situations in the middle and upper parts of the epithelium, while with dVIN patients, such staining was observed in only 45 women (29%). Conclusions. The determination of IHC markers p16, p53 and Ki67 allows to distinguish dVIN from VHSIL, especially in difficult diagnostic cases. In addition, the presence of mutant p53 indicates the possibility of rapid progression to cancer and requires immediate and more aggressive treatment and follow-up.